Dynamics of three-dimensional helical domain wall in cylindrical NiFe nanowires - Wong, De Wei (2015)
We report on a micromagnetic study on the dynamics of current-driven helical domain wall (DW) in cylindrical NiFe nanowires. The helical DW is a three-dimensional transition region between magnetizations with clockwise and anticlockwise vortex orientations. A minimum current density is needed to overcome an intrinsic pinning to drive the helical DW, and the propagation along the nanowire is accompanied by a rotational motion. As the driving current strength is increased, the rotation ceases while the DW propagates at an increased velocity. However, a velocity barrier is experienced which results in the decrease of the DW mobility. Throughout its motion, the propagated helical DW maintains a stable profile without showing any sign of structural breakdown even at relatively high driving current.